Abiraterone acetate after progression with enzalutamide in chemotherapy-naïve patients with metastatic castration-resistant prostate cancer: a multi-center retrospective analysis. (December 2016) - Yamada, Yoko; Matsubara, Nobuaki; Tabata, Ken-ichi; Satoh, Takefumi; Kamiya, Naoto; Suzuki, Hiroyoshi; Kawahara, Takashi; Uemura, Hiroji; Yano, Akihiro; Kawakami, Satoru
Abstract Background Both abiraterone acetate (AA) and enzalutamide are promising agents for patients with pre- and post-chemotherapy metastatic castration-resistant prostate cancer (mCRPC). Several retrospective analysis suggested clinical cross-resistance between these agents in patients previously treated with docetaxel. However, data on the antitumor activity of AA as a second androgen receptor-targeting new agent after the failure of enzalutamide in chemotherapy-naive mCRPC patients is unavailable. Methods Patients with chemotherapy-naïve mCRPC who were treated with AA after disease progression with enzalutamide, were retrospectively reviewed at five institutions. Primary outcome measure was the rate of any prostate-specific antigen (PSA) decline. Secondary outcome measures were progression-free survival (PFS) and overall survival (OS) with subsequent AA treatment. We also performed correlation analysis between previous PSA response, PFS duration to enzalutamide and subsequent PSA response, PFS duration to AA. Results A total of 14 patients were identified. Any PSA declines and PSA decline ≥50 % with AA treatment, were observed in 36 and 7 % of patients, respectively. Median PFS with initial enzalutamide was 5.0 months (95 % CI 3.7–6.4 months), and for subsequent AA treatment was 3.4 months (95 % CI 0.8–6.0 months). Median OS from initiation of AA was 9.1 months (95 % CI 5.6–12.5 months). No significant correlations were observed between these PSA responses (Pearson r = −0.67, p = 0.82) and PFS duration (Kendall tau r = 0.33, p = 0.87). Conclusions The PSA decline with subsequent AA treatment in chemotherapy-naive mCRPC patients after a failure of enzalutamide was modest, however, the PFS and OS with subsequent AA treatment were comparable to those of enzalutamide previously reported as a second androgen receptor-targeting new agent after AA failure. The PSA response and PFS duration to previous enzalutamide treatment did not predict those of subsequent AA treatment.